2010
DOI: 10.1101/cshperspect.a003566
|View full text |Cite
|
Sign up to set email alerts
|

Riboswitches and the RNA World

Abstract: SUMMARYRiboswitches are structured noncoding RNA domains that selectively bind metabolites and control gene expression (Mandal and Breaker 2004a;Coppins et al. 2007;Roth and Breaker 2009). Nearly all examples of the known riboswitches reside in noncoding regions of messenger RNAs where they control transcription or translation. Newfound classes of riboswitches are being reported at a rate of about three per year (Ames and Breaker 2009), and these have been shown to selectively respond to fundamental metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
522
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 572 publications
(548 citation statements)
references
References 74 publications
12
522
0
5
Order By: Relevance
“…11,35 The SAM riboswitch class is one of the most abundant, 36 especially in Gram-positive organisms, and is unique in that six distinct SAM riboswitch families have been reported to date that bind SAM in diverse ways. 3,11,24,36 The large diversity of SAM riboswitches likely reflects the importance of regulating SAM-related metabolic pathways. 3 SAM riboswitches exhibit very high affinity for SAM and strongly discriminate against SAM-related analogs such as S-adenosylhomocysteine (SAH), 33,34 which differs from SAM by the absence of a single methyl group and the associated positive charge on the sulfur atom.…”
Section: S-adenosylmethionine (Sam) Riboswitchesmentioning
confidence: 99%
See 2 more Smart Citations
“…11,35 The SAM riboswitch class is one of the most abundant, 36 especially in Gram-positive organisms, and is unique in that six distinct SAM riboswitch families have been reported to date that bind SAM in diverse ways. 3,11,24,36 The large diversity of SAM riboswitches likely reflects the importance of regulating SAM-related metabolic pathways. 3 SAM riboswitches exhibit very high affinity for SAM and strongly discriminate against SAM-related analogs such as S-adenosylhomocysteine (SAH), 33,34 which differs from SAM by the absence of a single methyl group and the associated positive charge on the sulfur atom.…”
Section: S-adenosylmethionine (Sam) Riboswitchesmentioning
confidence: 99%
“…3,11,24,36 The large diversity of SAM riboswitches likely reflects the importance of regulating SAM-related metabolic pathways. 3 SAM riboswitches exhibit very high affinity for SAM and strongly discriminate against SAM-related analogs such as S-adenosylhomocysteine (SAH), 33,34 which differs from SAM by the absence of a single methyl group and the associated positive charge on the sulfur atom. A study has reported the existence of SAH-sensing riboswitches, 37 indicating that SAM/SAH riboswitches exploit chemical differences between closelyrelated metabolites to prevent cellular misregulation, which is consistent with recently obtained crystal structures.…”
Section: S-adenosylmethionine (Sam) Riboswitchesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the unacylated tRNA Gly UCC is similar to the much smaller metabolic products that affect the riboswitch mechanisms controlling gene expression; the 5′UTR undergoes a conformational change with the binding of the ligand. 82 The tRNA Gly UCC is also predicted to bind to the 5′-GGA-3′ Specifier codon in Bacillus and Staphylococcus species glycyl T-box riboswitches. 83 …”
Section: Unmodified Wobble Position 34 and The Importance Of Position 32mentioning
confidence: 99%
“…The ability of RNA to engage in intramolecular base pairing is well established (Busan & Weeks, 2013). RBS elements can be disabled by intramolecular RNA folding, as is the case in riboswitches (Breaker, 2012). The RNA in riboswitches adopts an OFF state when the RBS is bound by a complementary anti-RBS sequence within the mRNA.…”
mentioning
confidence: 99%